Reflections on violence - Sorel, Georges, 1847-1922 (Cambridge texts in the history of political thought., 1999)
In this classic text, Sorel develops the ideas of violence, myth, and the general strike as the heroic actions of the proletariat. His ideas would later be cited by Marxists and Fascists to support their non-compliant and violent methods to strike at bourgeoisie culture.